PERSPECTIVES ON THE SUBJECT MODEL OF MENTAL TRAUMA AND POST-TRAUMATIC STRESS DISORDER - Starkov, Denys (TECHNOLOGIES OF INTELLECT DEVELOPMENT, 2023)
The article presents the perspectives of considering psychological trauma and related disorders, in particular post-traumatic stress disorder (PTSD), through the concept of subjectness - the subjectness model of psychological trauma. Psychic trauma is defined as an area of the self with a critical devaluation of subjectness. The concepts of subjectness are briefly reviewed, and three main aspects are highlighted: synthesizing, activity, and cognitive. The synthesizing function (aspect) of subjectivity is responsible for the formation of a holistic image of oneself, the world, and relationships - the more holistically an individual perceives the world and oneself, including one's life narrative in the form of a holistic autobiographical time, the higher the level of one's subjectivity. The cognitive function corresponds to the transfer of the sensory level of information to the abstract level and the creation, construction, and restructuring of mental models of the world by setting and solving problems. The synthesizing and cognitive function can be compared to such a concept as mentalization. The activity function corresponds to the individual's sense of himself as a free author of his life and ability to act in sense of a personal form of behavior in which he independently chooses goals and ways of achieving them, and/or an act of moral self-determination in which he asserts himself as a person. The activity function can be compared to such a concept as agency. It is shown that the critical devaluation of the synthesizing function of subjectness can describe the phenomenon of post-traumatic split personality, the devaluation of the activity function of subjectivity – a group of avoidance symptoms in PTSD and post-traumatic negative self-concept, the devaluation of the cognitive function – the inability to integrate the experience of traumatic stress and its existence in a dissociated sensory form. Examples of the author's models of post-traumatic splitting, devaluation of mentalization and formation of a negative self-concept through the formation of a complex of learned helplessness are presented. The concept of subjectness can be convenient for describing mental trauma because, on the one hand, it is holistic and humanistic. On the other hand, it allows working with individual functions of subjectness.